2021
DOI: 10.3389/fnins.2021.738442
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Neural Cell-Derived Exosomes in Intercellular Communication in Health and Neurodegenerative Diseases

Abstract: Intercellular communication in the central nervous system (CNS) is essential for brain growth, development, and homeostasis maintenance and, when dysfunctional, is involved in the occurrence and development of neurodegenerative diseases. Increasing evidence indicates that extracellular vesicles, especially exosomes, are critical mediators of intercellular signal transduction. Under physiological and pathological conditions, neural cells secret exosomes with the influence of many factors. These exosomes can car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 147 publications
0
42
0
Order By: Relevance
“…A lot of focus has been given to exosomes in neurodegenerative diseases, e.g., neuronal, astrocytic and oligodendrocytic exosomes [ 40 43 ], while the utility of other EV subtypes as biomarkers of neurodegenerative diseases has not yet been fully elucidated and requires further attention. Little evidence is available in the literature for MV alterations in neurodegeneration [ 44 ].…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…A lot of focus has been given to exosomes in neurodegenerative diseases, e.g., neuronal, astrocytic and oligodendrocytic exosomes [ 40 43 ], while the utility of other EV subtypes as biomarkers of neurodegenerative diseases has not yet been fully elucidated and requires further attention. Little evidence is available in the literature for MV alterations in neurodegeneration [ 44 ].…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…1 Another communication system that exists between neurons is the release of lipidbased transport systems such as exosomes from neurons following a synaptic response, that are taken up by neighboring cells [350,351]. Gabrielli et al [352] observed that endocannabinoids are secreted on extracellular membrane vesicles.…”
Section: Endogenous Receptors For Aea and 2-agmentioning
confidence: 99%
“…At present, the brain MSC-EVs, secreted by both neuronal and glial stroma cells, are recognized as versatile vesicles of communication, operative via molecules such as proteins, RNAs, lipids, and metabolites, involved in many processes: synaptic plasticity, nutritional metabolic support, nerve growth and regeneration, and mitigation of inflammatory processes. The properties of their cargoes and their membranes are largely known [ 44 , 45 , 46 ]. In various studies these vesicles have been shown to protect neurons from pathological processes; for example, from ischemic conditions [ 47 ].…”
Section: Role Of the Extracellular Vesicles From Mesenchymal Stem Cells: Recent Views About The Alzheimer’s Diseasementioning
confidence: 99%